Equity Mutual Fund Performance Analysis using Sharpe and Treynor Indices 2012-2013 - Septini Kumalaputri (Eduvest - Journal of Universal Studies, 2021)
This research examines stock mutual fund performance compared with market performance (IHSG) by Sharpe and Treynor approaches. The research problems are whether there are significant difference between stock mutual fund performance and market performance (IHSG) in Indonesia Stock Exchange (IDX) by Sharpe approach, whether there are significant difference between stock mutual fund performance and market performance (IHSG) in Indonesia Stock Exchange (IDX) by Treynor approach, and which one of stock mutual fund has the best performance if measured using Sharpe and Treynor approach. The sample in this research are 31 stock mutual fund listed in Indonesia Stock Exchange year 2012 to 2013 from 11 Investment Management which have the biggest AUM. The analysis used in this research is Independent Sample T-Test by SPSS version 16 program package. The results show that there is a significant difference between stock mutual fund performance with market performance used Sharpe Index and there is a significant difference between stock mutual fund performance with market performance used Treynor Index. Stock mutual fund which has the best performance if measured uses Sharpe and Treynor approach is Trim Kapital Plus. The findings implied that investors should use Treynor approach to evaluate the performance stock mutual fund because it is consistence. Meanwhile, investment managers must reconsider stock portofolio and the use of Treynor approach in evaluating performance stock mutual fund.